Budget Allocation for Thermodynamic and Mechanical Projects of an Organization - Don Pan, Bing; Amini, Mahyar; Shoushtari, Farzaneh (International journal of industrial engineering and operational research, 2023)
This paper investigates the application of optimization approaches for allocating budgets to thermodynamic and mechanical projects within an organization. By considering project attributes such as estimated return on investment (ROI), risk level, and alignment with strategic goals, the proposed methodology aims to optimize the overall project portfolio and maximize long-term organizational value. The paper begins with a review of existing budget allocation methods and their limitations. It then outlines the proposed optimization framework, detailing the objective function, constraints, and candidate solution space. Various optimization algorithms are then evaluated for their suitability and effectiveness in solving the budget allocation problem. Numerical results are presented and analyzed, demonstrating the potential of the proposed approach to generate efficient and strategically aligned project portfolios. Finally, the paper concludes by summarizing the key findings and outlining potential future research directions.